2008
DOI: 10.1212/01.wnl.0000304040.29080.7b
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers for response to interferon therapy in patients with multiple sclerosis

Abstract: Findings indicate that measurements of both myxovirus-resistance-protein A (MxA) and neutralizing antibodies (NAbs) predict the risk of new relapses; however, the slightly stronger prognostic significance of MxA mRNA and the easier method for it measurement make MxA mRNA the preferred biomarker for monitoring interferon beta (IFN beta)-treated patients. This information can be used to better tailor treatment to the individual patient with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 33 publications
4
58
1
Order By: Relevance
“…MxA gene expression levels above or below 87 RE correctly predicted the response to IFNb injection with a sensitivity of 92.44% and a specificity of 92.52%. The MxA mRNA threshold of 87 RE has recently been clinically validated and was shown to have a strong prognostic value for the risk of new relapses [1].…”
Section: Mxa Gene Expression Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…MxA gene expression levels above or below 87 RE correctly predicted the response to IFNb injection with a sensitivity of 92.44% and a specificity of 92.52%. The MxA mRNA threshold of 87 RE has recently been clinically validated and was shown to have a strong prognostic value for the risk of new relapses [1].…”
Section: Mxa Gene Expression Analysismentioning
confidence: 99%
“…Their identification can be made after 1 year of treatment, allowing for the utilization of alternative agents and saving huge amount of economical resources. In fact, a large number of papers have demonstrated that measurement of MxA is a reliable, easy to perform, pharmacogenomic marker of IFNb biological activity, and recently of clinical efficacy [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Another potential marker of biologic response to interferon therapy is the presence of myxovirus-resistance protein A (MxA), an antiviral protein exclusively induced by type 1 interferons. 28 Quantification of MxA expression might be a sensitive measure of IFN␤ activity.…”
Section: Biomarkers In Msmentioning
confidence: 99%